Lithostratigraphy and age of pre-Late Weichselian sediments in the Suupohja area, western Finland - Pitkäranta, Reijo (fi=Turun yliopisto|en=University of Turku|, 2013)
Different types of laterally extensive sand- and gravel-dominated deposits, up to several tens of metres thick, were investigated in the Suupohja area of western Finland. The studied sediments were deposited in glacial, ice-marginal, glaciofluvial, sea or lake, littoral and terrestrial environments during several glacial-non-glacial cycles. Seventeen pre-Late Weichselian and three Late Weichselian/Holocene sedimentary units were identified. These were divided into ten formally and two informally defined formations that were together termed the Suupohja Group. Every unit are nevertheless not detectable throughout the study area. The informally defined “Karhukangas lower deposits” represent the lowest units in the Suupohja Group. The Karhukangas lower deposits with 5 till units, 3 glaciolacustrine/-marine units and 2 sand units, were interpreted as having been deposited during possibly four glacial-non-glacial cycles before the Late Pleistocene Subepoch (MIS 6 or earlier). The Kankalo Sand above the Karhukangas lower deposits comprises glaciofluvial and aeolian sands of Late Saalian, Eemian or Early Weichselian origin (MIS 6–MIS 5c). The Kariluoma Till above the Kankalo Sand was possibly deposited during the Late Saalian glacial advance, although an Early Weichselian origin is also possible. The Harrinkangas Formation, with glaciofluvial and quiet-water sediments, is interpreted as having been deposited during the Late Saalian and Eemian Stages (MIS 6–MIS 5e). The uppermost units in the deposits studied, the Kodesjärvi Formation (shore deposit), Isojoki Sand (aeolian), Rävåsen Formation (glaciofluvial), Vanhakylä Formation (shore line deposit), Dagsmark Till and Kauhajoki Till, were deposited during the Weichselian Stage (MIS 5d–MIS 2). In addition, Early Holocene (MIS 1) eskers without till cover were informally termed the “Holocene esker deposits”. The Lumikangas Formation represents gravelly shore deposits formed in the Holocene Epoch, when these areas last emerged from the sea. The first Weichselian ice expansion possibly reached the western part of Suupohja in the Early Weichselian Substage (MIS 5d?), but it did not expand further to the east. The second Weichselian glaciation of relatively short duration occupied the southern part of Finland in the later part of Middle Weichselian (MIS 3). Thus, the southern half of the country remained ice-free for the majority (~65–75%) of the Weichselian Stage. Instead, both humid temperate and periglacial conditions alternated. In the initial part of Middle Weichselian, this area was partly submerged, which indicates eastward expansion of the Scandinavian ice sheet(s), depressing the lithosphere. The exceptionally thick sediment cover, multiple lithofacies, relict landscape and preserved preglacially weathered bedrock are evidence of weak glacial erosion in the Suupohja area during the latest as well as earlier glaciations, making this area one of the key areas in Quaternary research.